Školství jako veřejně poskytovaný soukromý statek - Nečasová, Romana (2008)
This paper explores the relationship between education and public sector. It examines broadly accepted notion that education is a legitimate and necessary function of the state. The notion is often based upon these reasons: an educated individual brings whole society a positive externality; the market will not provide equal opportunities; and education is a good which should be consumed by everyone. The study hence examines whether the market really fails in this area and whether the state provision is the best solution. Education is a politically sensitive topic, thus there exists social approach besides the economic one. Using historical line of a Czech school system, this paper shows how was the social approach formed and how it looks like today. It is concluded that public education is not the ideal form and possible solutions are propounded